Meningkatkan Disiplin Anak melalui Kegiatan Pretend Play Mini Market di Taman Kanak-Kanak Zahara Kota Bengkulu - Siti Patimah Nur; Nur Hazizah (Al-DYAS, 2026)
Discipline is an important aspect of early childhood social-emotional development. However, some children still experience difficulties in following rules, waiting for their turn, and completing tasks properly, including Group B children at TK Zahara, Bengkulu City. This condition indicates the need for learning activities that are engaging and appropriate to the developmental characteristics of young children. This study aimed to improve children’s discipline through a mini-market pretend play activity in Group B at TK Zahara, Bengkulu City. The study employed Classroom Action Research conducted in two cycles, with each cycle comprising the stages of planning, implementation, observation, and reflection. The research subjects consisted of 15 Group B children. Data were collected through observation and documentation. The results showed an improvement in children’s discipline at each stage of the intervention. In the pre-cycle stage, the average achievement of children’s discipline was 33%. Following the implementation of Cycle I, this achievement increased to 47%, categorized as developing, and then increased further to 80% in Cycle II, categorized as developing very well. Improvements in discipline were evident in the children’s ability to queue, follow the rules of the game, and complete tasks. This study concludes that the mini-market pretend play activity was effective in improving the discipline of Group B children at TK Zahara, Bengkulu City. These findings provide practical implications for teachers regarding the use of role-play as an engaging learning activity to stimulate discipline development in early childhood.